Keseimbangan Pasar Uang dalam Perspektif Ekonomi Islam - M. Ibnu Rizal; Nova Elisa; Suci Hayati (Indo Publishing, 2025)
The equilibrium of the money market within both conventional and Islamic economic systems. Using the IS-LM theoretical framework, it outlines the fundamental differences between the two systems, particularly in terms of the motives for money demand, monetary policy instruments, and their implications for economic stability. In Islamic economics, speculative motives are prohibited, and financial instruments must be free from usury (riba). The discussion also highlights the role of zakat and social responsibility in maintaining monetary equilibrium